Antibacterial composite glass fabric and preparation method thereof
By adopting a five -layer structure of bacteriostatic composite glass fiber cloth, the composition materials such as epoxy resin and nanomaterials are used to solve the lack of existing composite glass fiber cloth in terms of stretching and breaking strength and bacteriostatic performance. Material performance is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411478156.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
AI Technical Summary
The existing composite fiberglass cloth has shortcomings in tensile fracture strength and antibacterial properties, and it is difficult to meet the requirements of high fracture strength and strong antibacterial properties of materials in specific application scenarios.
It adopts a five-layer structure of antibacterial composite fiberglass cloth, in which the outermost two layers are antibacterial layers, the middle layer is fiberglass cloth layer, and between the antibacterial layer and fiberglass cloth layer is a metal layer. The antibacterial layer is composed of epoxy resin, fillers, curing agents, accelerators, solvents, inorganic nanomaterials and allylthiadiazole compounds. By regulating the hydrophilic and lipophilic properties of nanoscale titanium dioxide and allylthiadiazole compounds The mass ratio of the compound enhances the tensile breaking strength and antibacterial effect of the material.
It has significantly improved the stretching and fracture strength and bacteriostatic performance of composite glass fiber cloth, can more effectively prevent the breeding and spread of bacteria and fungi, and suitable for various application scenarios that require high -performance materials.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite cloths, and in particular to an antibacterial composite glass fiber cloth and a preparation method thereof. Background Art
[0002] Composite fiberglass cloth is a new type of material obtained by combining fiberglass cloth with other materials. Composite fiberglass cloth combines the advantages of fiberglass cloth and other materials and has more excellent performance. Composite fiberglass cloth not only maintains the original advantages of fiberglass cloth, but also broadens its application scope and meets the diverse demands for material performance in different fields.
[0003] In modern society, antibacterial properties are crucial for many materials. In the fields of construction, transportation, industry, etc., the antibacterial properties of materials can effectively prevent the growth and spread of microorganisms such as bacteria and fungi, and protect people's health and safety. For glass fiber cloth, especially in some specific application scenarios, such as antibacterial air duct pasting cloth, it is often necessary to perform bending, stretching and other operations to adapt to different installation spaces and layout requirements, and it is essential to have a certain breaking strength. Therefore, the development of a composite glass fiber cloth with high breaking strength and strong antibacterial properties has important practical significance and broad application prospects. Summary of the invention
[0004] The present invention provides an antibacterial composite glass fiber cloth and a preparation method thereof, which solves the problems of low tensile breaking strength and poor antibacterial performance of the composite glass fiber cloth in the related art.
[0005] The technical solution of the present invention is as follows: The present invention proposes an antibacterial composite glass fiber cloth, which is composed of five layers, the outermost two layers are antibacterial layers, the middle layer is a glass fiber cloth layer, and the metal layer is between the antibacterial layer and the glass fiber cloth layer. The antibacterial layer includes the following component raw materials in parts by weight: 60-80 parts of epoxy resin, 5-10 parts of filler, 6-8 parts of curing agent, 1-3 parts of accelerator, 10-20 parts of solvent, and 5-7 parts of antibacterial agent; The antibacterial agent consists of an inorganic nano material and an allyl thiadiazole compound, and the mass ratio of the inorganic nano material to the allyl thiadiazole compound is 2:1-2.
[0006] As a further technical solution, the inorganic nanomaterial includes one or more of nano titanium dioxide, nano copper oxide, and nano zinc oxide.
[0007] As a further technical solution, when the inorganic nanomaterial is nano titanium dioxide, the nano titanium dioxide consists of a first nano titanium dioxide and a second nano titanium dioxide, and the first nano titanium dioxide and the second nano titanium dioxide have different hydrophilic and lipophilic properties.
[0008] In the present invention, hydrophilic and lipophilic nano titanium dioxide are used as antibacterial agents at the same time. By adjusting the mass ratio of the two, the synergistic effect of the two is fully exerted, the dispersion stability in different systems is improved, and the tensile breaking strength and antibacterial effect are enhanced.
[0009] As a further technical solution, the first nano-titanium dioxide is hydrophilic, the second nano-titanium dioxide is lipophilic, and the mass ratio of the first nano-titanium dioxide to the second nano-titanium dioxide is 1:2-4.
[0010] As a further technical solution, the allyl thiadiazole compound includes one or more of 5-allylsulfonyl-[1,3,4]thiadiazole-2-amine, 3-amino-5-allylthio-1,2,4-thiadiazole, and N5-2-propylene-1-yl-1,2,4-thiadiazole-3,5-diamine.
[0011] As a further technical solution, the filler includes one or more of kaolin, montmorillonite and talc.
[0012] As a further technical solution, the curing agent includes one or more of ethylenediamine, diethylenetriamine, and meta-xylylenediamine.
[0013] As a further technical solution, at least one of the following technical features is included: The accelerator includes one or two of 2-methylimidazole and 2-ethyl-4-methylimidazole; The solvent includes one or more of toluene, xylene and ethyl acetate.
[0014] As a further technical solution, the preparation of the antibacterial layer includes the following steps: weighing the raw materials of the antibacterial layer, stirring and dispersing them evenly to obtain the antibacterial layer.
[0015] This scheme also proposes a method for preparing an antibacterial composite glass fiber cloth, comprising the following steps: S1, plating metal layers on both sides of the glass fiber cloth layer to obtain heat-resistant glass fiber cloth; S2. After the heat-resistant glass fiber cloth is dipped in the antibacterial layer, it is dried to obtain the antibacterial composite glass fiber cloth.
[0016] As a further technical solution, the thickness of the glass fiber cloth layer is 0.1-0.5 mm.
[0017] The working principle and beneficial effects of the present invention are: In the present invention, inorganic nanomaterials and allyl thiadiazole compounds are added as antibacterial agents to exert the synergistic effect of multiple antibacterial mechanisms and improve the antibacterial effect of the composite glass fiber cloth. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the following examples and comparative examples: The first nano titanium dioxide: hydrophilic, mixed crystal titanium dioxide (anatase: rutile = 4:1), average particle size 20nm, manufacturer is Bohuasi Nanotechnology (Ningbo) Co., Ltd.; Second nano titanium dioxide: lipophilic, mixed crystal titanium dioxide (anatase: rutile = 4:1), average particle size 20nm, manufacturer is Bohuasi Nano Technology (Ningbo) Co., Ltd.; Chitosan: food grade, effective content 99%, manufacturer is Blue Power Biotechnology (Xi'an) Co., Ltd.; Epoxy resin: Model E44; Metal layer: the material is aluminum, the thickness is 0.004mm; Glass fiber cloth layer: thickness is 0.5mm.
[0020] Example 1 Antibacterial layer: weigh 60 parts of epoxy resin, 5 parts of kaolin, 6 parts of ethylenediamine, 1 part of 2-methylimidazole, 10 parts of toluene, and 5 parts of antibacterial agent, stir and disperse them evenly to obtain an antibacterial layer, wherein the 5 parts of antibacterial agent include 1.25 parts of the first nano-titanium dioxide and 3.75 parts of 3-amino-5-allylthio-1,2,4-thiadiazole; A method for preparing an antibacterial composite glass fiber cloth comprises the following steps: S1. Hot-dip aluminum on both sides of the glass fiber cloth layer, the hot-dip liquid is molten aluminum liquid, the hot-dip temperature is 650°C, the hot-dip time is 4 minutes, and the temperature-resistant glass fiber cloth is obtained; S2. After the heat-resistant glass fiber cloth is dipped in the antibacterial layer, it is dried to obtain the antibacterial composite glass fiber cloth.
[0021] Example 2 Antibacterial layer: weigh 70 parts of epoxy resin, 8 parts of montmorillonite, 7 parts of diethylenetriamine, 2 parts of 2-methylimidazole, 15 parts of xylene, and 6 parts of antibacterial agent, stir and disperse them evenly to obtain an antibacterial layer, wherein the 6 parts of antibacterial agent include 1.5 parts of the first nano-titanium dioxide and 4.5 parts of 3-amino-5-allylthio-1,2,4-thiadiazole; A method for preparing an antibacterial composite glass fiber cloth comprises the following steps: S1. Hot-dip aluminum on both sides of the glass fiber cloth layer, the hot-dip liquid is molten aluminum liquid, the hot-dip temperature is 650°C, the hot-dip time is 4 minutes, and the temperature-resistant glass fiber cloth is obtained; S2. After the heat-resistant glass fiber cloth is dipped in the antibacterial layer, it is dried to obtain the antibacterial composite glass fiber cloth.
[0022] Example 3 Antibacterial layer: weigh 80 parts of epoxy resin, 10 parts of talc, 10 parts of m-xylylenediamine, 3 parts of 2-ethyl-4-methylimidazole, 20 parts of ethyl acetate, and 7 parts of antibacterial agent, stir and disperse them evenly to obtain an antibacterial layer, wherein the 7 parts of antibacterial agent include 1.75 parts of the first nano-titanium dioxide and 5.25 parts of 3-amino-5-allylthio-1,2,4-thiadiazole; A method for preparing an antibacterial composite glass fiber cloth comprises the following steps: S1. Hot-dip aluminum on both sides of the glass fiber cloth layer, the hot-dip liquid is molten aluminum liquid, the hot-dip temperature is 650°C, the hot-dip time is 4 minutes, and the temperature-resistant glass fiber cloth is obtained; S2. After the heat-resistant glass fiber cloth is dipped in the antibacterial layer, it is dried to obtain the antibacterial composite glass fiber cloth.
[0023] Example 4 Compared with Example 2, the difference of Example 4 is that 6 parts of the antibacterial agent include 4 parts of the first nano-titanium dioxide and 2 parts of 3-amino-5-allylthio-1,2,4-thiadiazole.
[0024] Example 5 Compared with Example 2, the difference of Example 5 is that 6 parts of the antibacterial agent include 3 parts of the first nano-titanium dioxide and 3 parts of 3-amino-5-allylthio-1,2,4-thiadiazole.
[0025] Example 6 Compared with Example 2, the difference of Example 6 is that 6 parts of the antibacterial agent include 2 parts of the first nano-titanium dioxide and 4 parts of 3-amino-5-allylthio-1,2,4-thiadiazole.
[0026] Example 7 Compared with Example 5, the difference of Example 7 is that 3 parts of the first nano-titanium dioxide are replaced by an equal amount of the second nano-titanium dioxide.
[0027] Example 8 Compared with Example 5, Example 8 is different in that 3 parts of the first nano-titanium dioxide are replaced by 1.5 parts of the first nano-titanium dioxide and 1.5 parts of the second nano-titanium dioxide.
[0028] Example 9 Compared with Example 5, Example 9 is different in that 3 parts of the first nano-titanium dioxide are replaced by 1 part of the first nano-titanium dioxide and 2 parts of the second nano-titanium dioxide.
[0029] Example 10 Compared with Example 5, Example 10 is different in that 3 parts of the first nano-titanium dioxide are replaced by 0.6 parts of the first nano-titanium dioxide and 2.4 parts of the second nano-titanium dioxide.
[0030] Embodiment 11 Compared with Example 5, Example 11 is different in that 3 parts of the first nano-titanium dioxide are replaced by 0.5 parts of the first nano-titanium dioxide and 2.5 parts of the second nano-titanium dioxide.
[0031] Example 12 Compared with Example 10, Example 12 is different in that 3 parts of 3-amino-5-allylthio-1,2,4-thiadiazole are replaced by an equal amount of 5-allylsulfonyl-[1,3,4]thiadiazole-2-amine.
[0032] Example 13 Compared with Example 10, Example 13 is different in that 3 parts of 3-amino-5-allylthio-1,2,4-thiadiazole are replaced by an equal amount of N5-2-propen-1-yl-1,2,4-thiadiazole-3,5-diamine.
[0033] Comparative Example 1 Compared with Example 2, the difference in Comparative Example 1 is that the antibacterial agent is replaced by an equal amount of chitosan.
[0034] Comparative Example 2 Compared with Example 2, the difference of Comparative Example 2 is that the 6 parts of the added antibacterial agent only include the first nano titanium dioxide.
[0035] Comparative Example 3 Compared with Example 2, the difference of Comparative Example 3 is that the 6 parts of antibacterial agent added only include 3-amino-5-allylthio-1,2,4-thiadiazole.
[0036] The antibacterial composite glass fiber cloths prepared in Examples 1 to 13 and Comparative Examples 1 to 3 were tested according to the following method: Antibacterial rate: According to the test method specified in GB / T 20944.2-2007 "Evaluation of antibacterial properties of textiles Part 2: Absorption method", the antibacterial rate of the test sample was tested. The test results are shown in Table 1 below: Table 1 Performance test results of antibacterial composite glass fiber cloths prepared in Examples 1 to 13 and Comparative Examples 1 to 3
[0037] Compared with Example 2, Comparative Example 1 adds chitosan as an antibacterial agent, Comparative Example 2 only adds the first nano-titanium dioxide as an antibacterial agent, and Comparative Example 3 only adds 3-amino-5-allylthio-1,2,4-thiadiazole as an antibacterial agent. The results show that the antibacterial rates of Example 2 against Escherichia coli and Staphylococcus aureus are greater than those of Comparative Examples 1 to 3, indicating that the first nano-titanium dioxide and 3-amino-5-allylthio-1,2,4-thiadiazole play a synergistic role and can improve the antibacterial properties of the composite glass fiber cloth. In Example 2 and Examples 4 to 6, different mass ratios of the first nano-titanium dioxide and 3-amino-5-allylthio-1,2,4-thiadiazole were added. As a result, the antibacterial rates of Examples 4 and 5 against Escherichia coli and Staphylococcus aureus were greater than those of Examples 2 and 6, indicating that when the mass ratio of the first nano-titanium dioxide and 3-amino-5-allylthio-1,2,4-thiadiazole was 2:1 to 2, the antibacterial performance of the obtained composite glass fiber cloth was better.
[0038] Compared with Example 10, Example 11 adds 5-allylsulfonyl-[1,3,4]thiadiazole-2-amine instead of 3-amino-5-allylthio-1,2,4-thiadiazole, and Example 12 adds N5-2-propylene-1-yl-1,2,4-thiadiazole-3,5-diamine instead of 3-amino-5-allylthio-1,2,4-thiadiazole. As a result, the antibacterial rates of Example 12 against Escherichia coli and Staphylococcus aureus are greater than those of Examples 11 and 13, indicating that when the added allyl thiadiazole compound is 5-allylsulfonyl-[1,3,4]thiadiazole-2-amine, the antibacterial performance of the obtained composite glass fiber cloth is better.
[0039] The glass fiber cloths prepared in Example 2 and Examples 7 to 11 were tested according to the following method: Tensile breaking strength: According to the test method specified in JC / T 996-2006 "Glass Fiber Wall Cloth", the tensile breaking strength of the glass fiber cloth was tested. The test results are shown in Table 2 below: Table 2 Performance test results of the antibacterial composite glass fiber cloth prepared in Example 2 and Examples 7 to 11
[0040] Compared with Examples 2 and 7, Examples 8 to 11 simultaneously add the first nano-titanium dioxide and the second nano-titanium dioxide. As a result, the warp and weft tensile breaking strengths of Examples 8 to 11 are greater than those of Examples 2 and 7, indicating that the first nano-titanium dioxide and the second nano-titanium dioxide play a synergistic role and can improve the tensile breaking strength of the glass fiber cloth. In Examples 8 to 11, different mass ratios of the first nano-titanium dioxide and the second nano-titanium dioxide are added. As a result, the warp and weft tensile breaking strengths of Examples 9 and 10 are greater than those of Examples 8 and 11, indicating that when the mass ratio of the first nano-titanium dioxide and the second nano-titanium dioxide is 1:2 to 4, the tensile breaking strength of the obtained glass fiber cloth is better.
[0041] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An antibacterial composite glass fiber cloth, characterized in that: The invention is composed of five layers, the two outermost layers are antibacterial layers, the middle layer is a glass fiber cloth layer, and the metal layer is between the antibacterial layer and the glass fiber cloth layer. The antibacterial layer comprises the following component raw materials in parts by weight: 60-80 parts of epoxy resin, 5-10 parts of filler, 6-8 parts of curing agent, 1-3 parts of accelerator, 10-20 parts of solvent, and 5-7 parts of antibacterial agent; the antibacterial agent is composed of inorganic nanomaterials and allyl thiadiazole compounds, and the mass ratio of the inorganic nanomaterials to the allyl thiadiazole compounds is 2:1-2.
2. The antibacterial composite glass fiber cloth according to claim 1, characterized in that: The inorganic nanomaterial includes one or more of nano titanium dioxide, nano copper oxide, and nano zinc oxide.
3. The antibacterial composite glass fiber cloth according to claim 1, characterized in that: When the inorganic nano material is nano titanium dioxide, the nano titanium dioxide consists of a first nano titanium dioxide and a second nano titanium dioxide, and the first nano titanium dioxide and the second nano titanium dioxide have different hydrophilic and lipophilic properties.
4. The antibacterial composite glass fiber cloth according to claim 3, characterized in that: The first nano-titanium dioxide is hydrophilic, the second nano-titanium dioxide is lipophilic, and the mass ratio of the first nano-titanium dioxide to the second nano-titanium dioxide is 1:2-4.
5. The antibacterial composite glass fiber cloth according to claim 1, characterized in that: The allyl thiadiazole compound includes one or more of 5-allylsulfonyl-[1,3,4]thiadiazole-2-amine, 3-amino-5-allylthio-1,2,4-thiadiazole, and N5-2-propylene-1-yl-1,2,4-thiadiazole-3,5-diamine.
6. The antibacterial composite glass fiber cloth according to claim 1, characterized in that: The filler includes one or more of kaolin, montmorillonite and talc.
7. The antibacterial composite glass fiber cloth according to claim 1, characterized in that: The curing agent includes one or more of ethylenediamine, diethylenetriamine, and meta-xylylenediamine.
8. The antibacterial composite glass fiber cloth according to claim 1, characterized in that: Also includes at least one of the following technical features: The accelerator includes one or two of 2-methylimidazole and 2-ethyl-4-methylimidazole; The solvent includes one or more of toluene, xylene and ethyl acetate.
9. The antibacterial composite glass fiber cloth according to claim 1, characterized in that: The preparation of the antibacterial layer comprises the following steps: The raw materials of the antibacterial layer are weighed, stirred and dispersed evenly to obtain the antibacterial layer.
10. The method for preparing an antibacterial composite glass fiber cloth according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, plating metal layers on both sides of the glass fiber cloth layer to obtain heat-resistant glass fiber cloth; S2. After the heat-resistant glass fiber cloth is dipped in the antibacterial layer, it is dried to obtain the antibacterial composite glass fiber cloth.